Analisis Perbedaan antara Bidan Delima dengan Non Delima dalam Pemberian Pelayanan KIA dan KBKR selama Masa Pandemi Covid-19 - Wahyu Nuraisya (Jurnal Sehat Mandiri, 2023)
The Covid-19 pandemic has had an impact on the life sector, one of which is the decline in the quality of midwifery services. The aim of this study was to analyze the differences between midwives in Delima and non-Delima in the delivery of Maternal and Child Health (MCH) and Reproductive Health Family Planning (KBKR) services during the Covid-19 Pandemic. The study was conducted comparatively with a cross-sectional approach. The research population was midwives supervising clinical practice students of the D3 Midwifery Study Program, STIKES Karya Husada Kediri. The sampling technique used simple random sampling, a sample of 92 respondents (delima and non-pomegranate midwives each 46 respondents). Data collection used a questionnaire from March 25 to July 26, 2021. Descriptive and bivariate univariate analysis techniques using the Mann Whitney test with a significance value (α=0.05) obtained all p values for each of the results of the analysis of differences in the status of pomegranate midwives and non-delima by providing pregnancy, delivery, post partum, postpartum, breastfeeding and family planning services > (more) than a significance value of α=0.05, it is stated that there is no difference between these variables. The conclusion is that there is no difference between the services provided by midwives with Delima midwife status and non-Delima midwives. Suggestions for further research other variables are the level of client satisfaction between the services of pomegranate and non pomegranate midwives.